Do Routine Preoperative and Intraoperative Urine Cultures Benefit Pediatric Vesicoureteral Reflux Surgery? - Daniel R. Hettel; Bradley C. Gill; Audrey C. Rhee (Advances in Urology)
Objective. To determine if routine preoperative and intraoperative urine cultures (UCx) are necessary in pediatric vesicoureteral (VUR) reflux surgery by identifying their association with each other, preoperative symptoms, and surgical outcomes. Materials and Methods. A retrospective review of patients undergoing ureteral reimplant(s) for primary VUR at a tertiary academic medical center between years 2000 and 2014 was done. Preoperative UCx were defined as those within 30 days before surgery. A positive culture was defined as >50,000 colony forming units of a single organism. Results. A total of 185 patients were identified and 87/185 (47.0%) met inclusion criteria. Of those, 39/87 (45%) completed a preoperative UCx. Only 3/39 (8%) preoperative cultures returned positive, and all of those patients were preoperatively symptomatic. No preoperatively asymptomatic patients had positive preoperative cultures. Intraoperative cultures were obtained in 21/87 (24.1%) patients; all were negative. No associations were found between preoperative culture results and intraoperative cultures or between culture result and postoperative complications. Conclusions. In asymptomatic patients, no associations were found between the completion of a preoperative or intraoperative UCx and surgical outcomes, suggesting that not all patients may require preoperative screening. Children presenting with symptoms of urinary tract infection (UTI) prior to ureteral reimplantation may benefit from preoperative UCx.